2019
DOI: 10.3389/fneur.2019.00353
|View full text |Cite
|
Sign up to set email alerts
|

Measuring Change Over Time: A Systematic Review of Evaluative Measures of Cognitive Functioning in Traumatic Brain Injury

Abstract: Objectives: The purpose of evaluative instruments is to measure the magnitude of change in a construct of interest over time. The measurement properties of these instruments, as they relate to the instrument's ability to fulfill its purpose, determine the degree of certainty with which the results yielded can be viewed. This work systematically reviews all instruments that have been used to evaluate cognitive functioning in persons with traumatic brain injury (TBI), and critically assesses their eva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 88 publications
(213 reference statements)
0
9
0
Order By: Relevance
“…It may also be difficult to interpret the clinical relevance of a small but statistically significant individual decline in the mean values over time, and whether this negative result induces further cognitive evaluation and relevant treatment for the individual. A recent review of cognitive measures in TBI (D'Souza et al, 2019) revealed that there is insufficient evidence for the test-retest reliability and responsiveness of instruments for measuring longitudinal change in cognition in TBI samples. Unfortunately, this may apply for the majority of neuropsychological tests used in this study, and we can question if there was a decline or a period of stability in cognitive functioning.…”
Section: Discussionmentioning
confidence: 99%
“…It may also be difficult to interpret the clinical relevance of a small but statistically significant individual decline in the mean values over time, and whether this negative result induces further cognitive evaluation and relevant treatment for the individual. A recent review of cognitive measures in TBI (D'Souza et al, 2019) revealed that there is insufficient evidence for the test-retest reliability and responsiveness of instruments for measuring longitudinal change in cognition in TBI samples. Unfortunately, this may apply for the majority of neuropsychological tests used in this study, and we can question if there was a decline or a period of stability in cognitive functioning.…”
Section: Discussionmentioning
confidence: 99%
“…Working memory was assessed using the WAIS III–Inverse digits (T15) and verbal memory using the Rey Auditory Verbal Memory Test (RAVLT) ( 28 ), specifically RAVLT learning (T17), RAVLT free-recall memory (T18) and RAVLT recognition (T19) ( 29 ).…”
Section: Methodsmentioning
confidence: 99%
“…It was piloted in Medline using medical subject headings (MeSH) and refined using key articles found in preliminary searches. 14 15 The Medline (Ovid interface) search strategy was consistent across all databases (online supplemental table 1). Strategic search terms included paediatric, child, adolescent, traumatic brain injury, head injury, cognition and neurocognitive disorder.…”
Section: Search Strategymentioning
confidence: 99%